2015
DOI: 10.1016/j.tetlet.2015.01.029
|View full text |Cite
|
Sign up to set email alerts
|

LiOO t -Bu as a terminal oxidant in a titanium alkoxide-mediated [2+2+2] reaction cascade

Abstract: LiOOt-Bu is an effective oxidant for converting the penultimate organometallic intermediate generated in a titanium alkoxide-mediated [2+2+2] reaction cascade to an allylic alcohol. Oxidation of the presumed allylic titanium species is highly regioselective, providing direct access to substituted hydroindanes containing a primary allylic alcohol. In addition to demonstrating the feasibility of this oxidation process, we document the ability to convert the primary allylic alcohol products to angularly substitut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…7 This result is consistent with the conclusion that, while the alkyne–alkyne coupling remains effective for this substrate class, there exists a larger energetic barrier for intramolecular cycloaddition in comparison to that associated with the annulation processes previously achieved for the convergent synthesis of hydrindanes. 46 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…7 This result is consistent with the conclusion that, while the alkyne–alkyne coupling remains effective for this substrate class, there exists a larger energetic barrier for intramolecular cycloaddition in comparison to that associated with the annulation processes previously achieved for the convergent synthesis of hydrindanes. 46 …”
Section: Resultsmentioning
confidence: 99%
“…Also, while one could imagine a rich reactivity profile associated with the metallacyclopentene intermediate 3 , we have been able to divert its reactivity away from standard cheletropic extrusion of Ti(O i -Pr) 2 only by one of two elimination pathways ( en route to 5 or 6 ). 5, 6 Here, we report a substantial advance in this general area of chemical reactivity, defining a means to realize intermolecular alkoxide-directed titanium-centered [2+2+2] annulation chemistry for the synthesis of angularly substituted decalins, and discovering that the resulting metallacyclopentene intermediates formed on cycloaddition ( 3 , n = 1) can be coerced down distinct reaction pathways en rote to more stereochemically complex products. Our studies have resulted in convergent annulation reactions that can be terminated not only by ligand induced cheletropic extrusion ( 7 ) but also by site- and stereoselective protonation ( 8 – 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…To access functionalized allylic alcohols like 41 , we decided to explore if the presumed penultimate organometallic species in the cascade reaction (a complex allylic titanium species) could be regioselectively oxidized. As depicted in Figure B, it was found that oxidation could be realized by quenching the annulation process with LiOO t ‐Bu . In contrast to the protonation experiments previously described, where the major product was formed from functionalization at the ring fusion, this oxidation selectively functionalizes the primary carbon of the system and leads to the desired allylic alcohol isomer.…”
Section: Hydroxyl Directed Metallacycle‐mediated Cross‐couplingmentioning
confidence: 83%
“…As depicted in Figure 9B, it was found that oxidation could be realized by quenching the annulation process with LiOO t -Bu. [22] In contrast to the protonation experiments previously described, where the major product was formed from functionalization at the ring fusion, this oxidation selectively functionalizes the primary carbon of the system and leads to the desired allylic alcohol isomer.…”
Section: Hydroxyl Directed Metallacycle-mediated Cross-couplingmentioning
confidence: 96%
“…In 2017, Micalizio group reported an interesting and concise approach based on the metallacycle‐mediated cross‐coupling to access a series of natural and enantiomeric steroids. [20c] The strategy involves the early construction of the C/D ring system via a metallacycle‐mediated annulative cross coupling, between an alkyne and a suitably functionalized chiral enyne followed by a strategic formation of the C5–C6 bond after a suitable functionalization and activation of ACD tricycle. The enyne 24 was synthesized from (–)‐epichlorohydrin either via a low yielding two‐step protocol involving 1) S N 2 displacement of the chloride by alkynyllithium derived from phenylpropargyl ether and 2) opening of the epoxide by propenyl cuprate or a more efficient three‐step protocol involving 1) opening of the epoxide by alkynyllithium in presence of BF 3 · Et 2 O, 2) treating with KO t Bu and 3) S N 2 displacement with propenyl cuprate.…”
Section: Syntheses Enabled By Transition Metal Catalysismentioning
confidence: 99%